2018
DOI: 10.1016/j.jvir.2018.05.009
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Analysis of the Prospective Multicenter SENTRY Clinical Trial: Safety and Effectiveness of the Novate Sentry Bioconvertible Inferior Vena Cava Filter

Abstract: The Sentry IVC filter provided safe and effective protection against PE, with a high rate of intended bioconversion and a low rate of device-related complications, through 12 months of imaging-intense follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Outcomes through 1 year of follow-up in the SENTRY clinical trial, which have been previously presented (12), are summarized in Appendix C (available online on the article's Supplemental Material page at www.jvir.org). Figure 2 shows the bioconversion status for all patients with imaging assessment at 6, 12, and 24 months.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Outcomes through 1 year of follow-up in the SENTRY clinical trial, which have been previously presented (12), are summarized in Appendix C (available online on the article's Supplemental Material page at www.jvir.org). Figure 2 shows the bioconversion status for all patients with imaging assessment at 6, 12, and 24 months.…”
Section: Resultsmentioning
confidence: 99%
“…The SENTRY clinical trial design was previously reported (12). This prospective, multicenter, nonrandomized, singlearm trial was conducted at 23 sites in the United States (n ¼ 20), Belgium (n ¼ 2), and Chile (n ¼ 1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations